Strategies for sustained release of heparin: A review. (15th October 2022) - Yang, Xuewen; Wang, Qiuxiang; Zhang, Aiwen; Shao, Xinyao; Liu, Tianqing; Tang, Bo; Fang, Guihua
Abstract: Heparin, a sulfate-containing linear polysaccharide, has proven preclinical and clinical efficacy for a variety of disorders. Heparin, including unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), and ultra-low-molecular-weight heparin (ULMWH), is administered systematically, in the form of a solution in the clinic. However, it is eliminated quickly, due to its short half-life, especially in the case of UFH and LMWH. Frequent administration is required to ensure its therapeutic efficacy, leading to poor patient compliance. Moreover, heparin is used to coat blood-contacting medical devices to avoid thrombosis through physical interaction. However, the short-term durability of heparin on the surface of the stent limits its further application. Various advanced sustained-release strategies have been used to prolong its half-life in vivo as preparation technologies have improved. Herein, we briefly introduce the pharmacological activity and mechanisms of action of heparin. In addition, the strategies for sustained release of heparin are comprehensively summarized.